2020
DOI: 10.3390/ijerph17217735
|View full text |Cite
|
Sign up to set email alerts
|

Mind-Mindedness and Parenting Stress: A Cross-Sectional Study in a Cohort of Mothers of 3-Month-Old Full-Term and Preterm Infants

Abstract: The preterm birth of a child is a sudden event that can disturb the overall family system and its functioning. Many studies have been conducted with the aim of exploring how and the degree to which this event affects the early mother–infant dyadic relationship and maternal well-being, with often mixed findings. The present study investigates the combined effect of preterm birth and parenting stress on mind-mindedness, a parenting dimension that captures how parents represent and treat their children as separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 64 publications
(100 reference statements)
2
10
1
Order By: Relevance
“…The EACI is provided through an individual, mutual discussion in a dialogue manner, focusing on both parents and infant simultaneously. This builds upon previous research showing that intervention programs targeting the relationship between preterm infants and their parents should be individualized [ 31 , 38 ] and target both the preterm infant and the parents [ 30 ]. Preterm birth impacts the expected new role as a parent [ 39 ].…”
Section: Discussionmentioning
confidence: 76%
“…The EACI is provided through an individual, mutual discussion in a dialogue manner, focusing on both parents and infant simultaneously. This builds upon previous research showing that intervention programs targeting the relationship between preterm infants and their parents should be individualized [ 31 , 38 ] and target both the preterm infant and the parents [ 30 ]. Preterm birth impacts the expected new role as a parent [ 39 ].…”
Section: Discussionmentioning
confidence: 76%
“…According to the World Health Organization (3), an infant is considered premature if born before completing 37 weeks of gestation. Preterm birth is considered a risk factor for the infant, potentially negatively affecting several areas of the infant's development, with the risk increasing as a function of the severity of prematurity (4). Indeed, premature infants often display a variety of short-and long-term motor, language and communication, cognitive and behavioral developmental delays (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis reported an increased risk of postpartum depression among mothers of premature infants ( 10 ). In addition, prematurity may interfere, either directly or indirectly, with the mother's parental self-image ( 4 ), parenting satisfaction and parental sense of efficacy ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other studies suggest that the differences between preterm and full-term samples are not revealed by group comparisons but are instead detected by analysing the interplay between risk and protective factors. A first study finds that even if the preterm and full-term groups do not differ in parenting stress level and mind-mindedness (the caregivers’ representation of a child’s mental life), the mothers of preterm infants with higher stress show more non-attuned comments with their children [ 7 ]. In a second study, preterm (<37 weeks of gestation) and full-term late talkers do not differ in child language measures and parental speech input at 30 months [ 8 ].…”
mentioning
confidence: 99%